Comportamento de mergulho do boto-cinza, Sotalia guianensis, na enseada do Curral, Praia de Pipa-RN, Brasil :possíveis adaptações cardíacas ao mergulho - Garri, Rosana Griselda (2006)
The marine tucuxi, Sotalia guianensis, is one of the smallest known cetaceans, has coastal habits, and occurs from Hondures to Santa Catarina, in southern Brazil. The objective of this dissertation was to describe diving behavior of the marine tucuxi in three age classes and to analyze the cardiac capacity to dive through the examination of hearts of stranded specimens. Observations were made from October 2004 to November 2005 from a vantage point, in Curral Bay at Pipa beach-RN. We used Ad Libitum sampling and All occurrences to record the behaviors. The diving was characterized by the total exposition of the tail fluke for a few seconds, in 90° or 45° angles. Were recorded 131 dives in three behavioral contexts: foraging, traveling and socialization. The difference between juveniles and adults in dive time and fluke out at 45° or 90° to search and/or capture prey is probably influenced by the strategy used and ability to capture the prey. The frequency of fluke out at 90° for foraging in adults may be related to increased physiological efficiency of adults in comparison to juveniles. However, in the context of travel and socialization the dive time and fluke out were independent between the age classes. Dive in calves were frequent during socialization (play behavior) and traveling. This, associated with synchronic calve-adult diving suggests that a relationship of these behaviors and the acquisition of experience and foraging skills. As observed in other cetaceans, the heart (n=12) of the estuarine dolphin is broad and presents long ventricles which form a round apex. The right ventricle is long and narrow. The degree of dilatation of the aortic bulb may support the heart during diastole. The characteristic morphology of the heart and short dive duration < 2 min and depth ranged from 10m in the estuarine dolphin, can be likely at physiological adaptation for diving, typical de dolphins with coastal habits. The limitation of diving time in this specie may be influenced by anatomical and physiological restrictions